Alternativas para o processamento do gás natural do Espírito Santo - Altenerath, Kelen Carolina (2023)
Natural gas has been presenting an increase in demand on the recent years, largely due to its competitive advantages over other fossil fuels. However, in Brazil, its production and supply chain remains under one dominant agent, which makes it difficult for new ones to enter the market and often causes other producers to dispose of their production with little or no financial return. Therefore, the objective of this work is to identify alternative natural gas processing technologies, to allow other natural gas producing companies to process and commercialize their natural gas production without depending on the infrastructure belonging to the dominant agent, considering the technical and regulatory limitations applicable to the activity, to minimize the effects of monopoly influence on the production chain and, finally, to guide the design of new production arrangements that enable the expansion of the supply of salable gas in the country. As a result, three technologies were identified that are already being applied in other countries, which are: compressed natural gas, liquefied natural gas and gas to liquids.